2010
DOI: 10.1097/gme.0b013e3181e664dc
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor symptoms and coronary artery calcium in postmenopausal women

Abstract: Objective-We assessed whether vasomotor symptoms (VMS) were associated with coronary artery calcium (CAC) and how hormone therapy may influence this association.Address for Correspondence: Matthew A. Allison, MD, MPH, 9500 Gilman Drive, Mailcode 0965, La Jolla, CA 92093-0965, 858-822-7671 (W)/858-822-7662 (F), mallison@ucsd.edu. Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 49 publications
1
19
0
2
Order By: Relevance
“…14 Furthermore, for IMT and CAC the opposite findings have also been reported, 3,11 and the Rancho Bernardo Study reported a reduced rate of mortality caused by cardiovascular disease (CVD) in women reporting night sweats, but not hot flushes. 15 To our knowledge, only two previous studies have investigated the associations between VMS and incident CVD, and their findings are contradictory.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…14 Furthermore, for IMT and CAC the opposite findings have also been reported, 3,11 and the Rancho Bernardo Study reported a reduced rate of mortality caused by cardiovascular disease (CVD) in women reporting night sweats, but not hot flushes. 15 To our knowledge, only two previous studies have investigated the associations between VMS and incident CVD, and their findings are contradictory.…”
Section: Introductionmentioning
confidence: 80%
“…Both the opposite findings and null findings have also been reported, however. 3,[11][12][13][14] The main limitation of most previous studies is their cross-sectional design, which makes it difficult to draw firm conclusions regarding causal pathways. Until now, only three prospective studies have examined the associations of hot flushes and night sweats with CHD incidence or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies reporting on the association of hot flushes, night sweats or combined (presence, history, duration or severity) and CAC were consistent in showing no association [14,31,36,37]. One study showed no cross-sectional association between severity of hot flashes or night sweats and IMT [37].…”
Section: Vasomotor Symptoms and Surrogate Cvd Markersmentioning
confidence: 92%
“…After the initial screening based on titles and abstracts, 103 articles in full text were extracted for further evaluation. In the full-text assessment, 16 of these articles and 11 unique studies [12][13][14][15][31][32][33][34][35][36][37] met our inclusion criteria and were included in the current systematic review and meta-analysis. Of the 87 articles excluded following full text evaluation, 60 were based on unrelated exposures, 14 did not report relevant risk estimates and 13 were duplicate publications.…”
Section: Literature Searchmentioning
confidence: 99%